Financial Performance of Consumer Goods Industry in Indonesia Before and During Covid-19 Pandemic - Andi Wijayanto; Agus Hermani Daryanto Seno (University of Merdeka Malang, 2022)
The global business world has been severely impacted by the Covid-19 pandemic. Many businesses from large to small have to struggle to survive in the midst of the difficulty of managing and maintaining a business, and the consumer goods industry in Indonesia is no exception. This study was conducted with the aim of knowing and proving the differences in the financial performance of manufacturing companies in the consumer goods industry sector in Indonesia before and during the Covid-19 pandemic. The sample studied consisted of 46 companies belonging to the Consumer Goods Industry sector that went public on the Indonesia Stock Exchange which were taken using purposive sampling technique. Methods of data collection using documentation techniques. The data source is obtained from the Indonesia Stock Exchange. Data analysis techniques include descriptive and inferential analysis using Paired Sample t-test. This study concludes that during the Covid-19 Pandemic, financial performance as indicated by the ROA ratio decreased significantly compared to before the Covid-19 Pandemic. Meanwhile, the ROE of consumer goods industry companies in Indonesia did not differ significantly before and during the Covid-19 pandemic.